Attitude of Four General Conference Seventh-day Adventist Run Higher Education Institution’s Administrators about Internationalization of Higher Education Institutions - Gladstone, Ranjith Kingston (8ISC Abstract Proceedings, 2022)
The Seventh-day Adventist Church's General Conference (GC) oversees several institutions and organizations worldwide. There are 118 Adventist tertiary institutions within which there are four listed institutions directly managed by the GC. They are a) The Adventist International Institute of Advanced Studies (AIIAS); b) Andrews University is the oldest Seventh-day Adventist educational institution; c) With its headquarters located in Nairobi, Kenya, Adventist University of Africa features both a graduate school and a seminary; and d) Best known for its medical school, Loma Linda University (LLU) is a Seventh-day Adventist health science university in Loma Linda, California. The administrators of these institutions are directly under the supervision of the GC officers. And they clearly understand that Internationalization is one of the core priorities for achieving international excellence in education. Therefore, these administrators should have the right attitude towards Internationalization. This is a quantitative study where the perspective of the administrators will be measured using a validated instrument with a Likert scale. The setting of the study will be at the four institutions, and the sampling will be a convenient sampling of all the available administrators of these institutions. The questionnaires will be sent through e-mail after the ethical board clearance and the gatekeepers. The results will be analyzed using SPSS. The results will be interpreted to report the level of attitude of these administrators towards Internationalization. Recommendations will be made in relation to the findings for these institutions. Keywords : Internationalization, GC Institutions, Administrators, International higher education institution, Quantitative Study